Herbivores on native and exotic Senecio plants: is host switching related to plant novelty and insect diet breadth under field conditions?. Issue 5 (26th December 2013) - Castells, Eva; Morante, Maria; Goula, Marta; Pérez, Nicolas; Dantart, Jordi; Escolà, Anna; Schonrogge, Karsten; Gange, Alan
Abstract Native herbivores can establish novel interactions with alien plants after invasion. Nevertheless, it is unclear whether these new associations are quantitatively significant compared to the assemblages with native flora under natural conditions. Herbivores associated with two exotic plants, namely Senecio inaequidens and S. pterophorus, and two coexisting natives, namely S. vulgaris and S. lividus, were surveyed in a replicated long‐term field study to ascertain whether the plant–herbivore assemblages in mixed communities are related to plant novelty and insect diet breadth. Native herbivores used exotic Senecio as their host plants. Of the 19 species of Lepidoptera, Diptera, and Hemiptera found in this survey, 14 were associated with the exotic Senecio plants. Most of these species were polyphagous, yet we found a higher number of individuals with a narrow diet breadth, which is contrary to the assumption that host switching mainly occurs in generalist herbivores. The Senecio specialist Sphenella marginata (Diptera: Tephritidae) was the most abundant and widely distributed insect species (ca. 80% of the identified specimens). Sphenella was associated with S. lividus, S. vulgaris and S. inaequidens and was not found on S. pterophorus. The presence of native plant congeners in the invaded community did not ensure an instantaneous ecological fitting between insects and alien plants. We conclude that novel associations between native herbivores and introduced Senecio plants are common under natural conditions. Plant novelty is, however, not the only predictor of herbivore abundance due to the complexity of natural conditions.